Effect of neat and reinforced polyacrylonitrile nanofibers incorporation on interlaminar fracture toughness of carbon/epoxy composite. Issue 2 (March 2018) - Razavi, S.M.J.; Neisiany, R. Esmaeely; Khorasani, S. Nouri; Ramakrishna, S.; Berto, F.
HIGHLIGHTS: Al2 O3 nanoparticles were incorporated in PAN nanofiber to be used in reinforcement of carbon/epoxy composites.. The carbon/epoxy composite panels were reinforced with Al2 O3 -PAN and PAN nanofibers. Fracture tests were conducted on DCB specimens to study the interlaminar fracture behavior of reinforced composites. Al2 O3 -PAN nanofiber reinforced composites had higher fracture energy improvements compared to the PAN nanofiber reinforced composites. ABSTRACT: This paper presents an experimental investigation on fracture behavior of epoxy resin-carbon fibers composites interleaved with both neat polyacrylonitrile (PAN) nanofibers and Al2 O3 -PAN nanofibers. In particular, the paper focuses on the effect of adding Al2 O3 nanopartiles in PAN nanofibers, which were incorporated in unidirectional (UD) laminates. The effectiveness of adding a thin film made of Al2 O3 -PAN on the fracture behavior of the carbon fiber reinforced polymer (CFRP) has been addressed by comparing the energy release rates, obtained by testing double cantilever beam (DCB) samples under mode I loading condition. A general improvement in interlaminar fracture energy of the CFRP is observed when the both neat PAN nanofibers and Al2 O3 -PAN nanofibers are interleaved. However, higher interlaminar strength has been observed for the samples with a thin film of Al2 O3 -PAN nanofibers, suggesting a better stress distribution and stress transformation from resin-rich area to reinforcement phase of hybrid composites. Graphical Abstract: This paper presents an experimental investigation on fracture behavior of epoxy resincarbon fibers composites interleaved with both neat polyacrylonitrile (PAN) nanofibers and Al2 O3 -PAN nanofibers. In particular, the paper focuses on the effect of adding Al2 O3 nanopartiles in PAN nanofibers, which were incorporated in unidirectional (UD) laminates. The effectiveness of adding a thin film made of Al2 O3 -PAN on the fracture behavior of the carbon fiber reinforced polymer (CFRP) has been addressed by comparing the energy release rates, obtained by testing double cantilever beam (DCB) samples under mode I loading condition. A general improvement in interlaminar fracture energy of the CFRP is observed when the both neat PAN nanofibers and Al2 O3 -PAN nanofibers are interleaved. However, higher interlaminar strength has been observed for the samples with a thin film of Al2 O3 -PAN nanofibers, suggesting a better stress distribution and stress transformation from resin-rich area to reinforcement phase of hybrid composites.